The intentions of thunder : new and selected poems - Smith, Patricia, 1955- (Scribner, an imprint of Simon & Schuster, LLC, 2025)
"The Intentions of Thunder gathers, for the first time, the essential work from across Patricia Smith's decorated career. Here, Smith's poems, affixed with her remarkable gift of insight, present a rapturous ode to life. With careful yet vaulting movement, these poems traverse the redeeming landscape of pain, confront the frightening revelations of history, and disclose the joyous possibilities of the future. The result is a profound testament to the necessity of poetry--all the careful witness, embodied experience, and bristling pleasure that it bestows--and of Smith's necessary voice." --